The miraculous baby - Khan, Saniyasnain (GoodWordKidz : India, 2011)
The story begins with Maryam (Mary), who is chosen by Allah to be the mother of a special child. Despite the challenges and the miraculous nature of her pregnancy, Maryam remains steadfast in her faith. The birth of Isa is portrayed as a sign of Allah's power and mercy. The book emphasizes themes of faith, trust in Allah, and the importance of understanding and respecting religious figures. Through simple language and illustrations, it aims to teach children about the miracles associated with Prophet Isa's birth and his role in Islamic teachings.